ANALISIS PRAKTIK MINDRING DALAM PERSPEKTIF EKONOMI ISLAM DI DESA MANYAR SIDORUKUN GRESIK - Zakiyyati, Qurrota Ayun; Prabowo, Prayudi Setiawan (Universitas Negeri Surabaya, 2020)
This Study uses a qualitative descriptive method that aims to determine proces of mindring practice services in the village of Manyar Sidorukun Gresik. From this study it can can be concluded, that mindring transaction have been going on for dozen of years and are considered as a solution to the household Economy that is easy and fast by using mutual trust. The concept of mindring practice is a service that offers credit sale and purchase with 2 objects namely the object of goods and money. In Islamic economic law the practice of mindring type of goods credit is in accordance with Fatwa No. 110 / DSN-MUI / IX / 2017 concerning sale and purchase agreement and does not include transactions containing usury. Whereas in the practice of mindring the type of money credit is not in accordance with Fatwa concerning the sale and purchase agreement on the provisions of the goods, because the goods referred to in the sale and purchase agreement of credit money are intangible only words, then the contract This money credit includes a loan agreement which contains usury because there are additional requirements that required by mindring practice service provider so that the law is haram.